2016
DOI: 10.1016/j.euroneuro.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Brain circuitry of compulsivity

Abstract: Compulsivity is associated with alterations in the structure and the function of parallel and interacting brain circuits involved in emotional processing (involving both the reward and the fear circuits), cognitive control, and motor functioning. These brain circuits develop during the pre-natal period and early childhood under strong genetic and environmental influences. In this review we bring together literature on cognitive, emotional, and behavioral processes in compulsivity, based mainly on studies in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
178
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 280 publications
(193 citation statements)
references
References 173 publications
10
178
1
Order By: Relevance
“…Various magnetic resonance imaging (MRI) techniques including three‐dimensional structural MRI scans, diffusion tensor imaging (DTI), and functional MRI (fMRI) have been used in numerous studies to investigate the neuropathological mechanisms of OCD. Researchers have proposed that abnormalities of the brain circuits involved in emotional processing (involving both the reward and the fear circuits), cognitive control, and motor functioning play an important role in its pathophysiology (van den Heuvel, van Wingen, Soriano‐Mas, Alonso, & Chamberlain, ). These brain circuits involve extensive brain regions such as orbitofrontal cortex (OFC), dorsolateral prefrontal cortex (DLPFC), and default mode network (DMN) (Chamberlain et al., ; Menzies et al., ; Modell, Mountz, Curtis, & Greden, ; Piras, Piras, Chiapponi, & Girardi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Various magnetic resonance imaging (MRI) techniques including three‐dimensional structural MRI scans, diffusion tensor imaging (DTI), and functional MRI (fMRI) have been used in numerous studies to investigate the neuropathological mechanisms of OCD. Researchers have proposed that abnormalities of the brain circuits involved in emotional processing (involving both the reward and the fear circuits), cognitive control, and motor functioning play an important role in its pathophysiology (van den Heuvel, van Wingen, Soriano‐Mas, Alonso, & Chamberlain, ). These brain circuits involve extensive brain regions such as orbitofrontal cortex (OFC), dorsolateral prefrontal cortex (DLPFC), and default mode network (DMN) (Chamberlain et al., ; Menzies et al., ; Modell, Mountz, Curtis, & Greden, ; Piras, Piras, Chiapponi, & Girardi, ).…”
Section: Introductionmentioning
confidence: 99%
“…In OCD, abnormally high degree connectivity of the OFC and the basal ganglia (Beucke et al, 2013; Hou et al, 2014), and positive correlations between OCD symptom severity and degree connectivity of the OFC and striatum were found in unmedicated patients. Importantly, contemporary neuroanatomical models of OCD (Milad and Rauch, 2012) and compulsivity (van den Heuvel et al, 2015) suspect abnormalities not only in frontostriatal, but also in limbic circuits, referencing observations of heightened responses of the amygdala in some symptom provocation studies (Breiter et al, 1996; Simon et al, 2014; Simon et al, 2010), and during processing of OCD-related words (van den Heuvel et al, 2005), respectively, in patients with OCD. Still there have been very few neuroimaging studies in BDD, and no study has investigated degree connectivity in participants with BDD to date.…”
Section: Introductionmentioning
confidence: 85%
“…In addition to these similarities in clinical phenotype, the recent change in classification intensifies efforts studying all OCRD to understand the brain circuitry of compulsivity (van den Heuvel et al, 2015), and motivates the search for neurobiological abnormalities common to intensively (such as OCD) and less intensively studied OCRD (such as BDD). For example, a recent study predicted and confirmed lower striatal dopamine D 2/3 receptor availability in BDD based on previous examinations of patients with OCD (Denys et al, 2004; Figee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although these disorders all share the core feature of repetitive behaviors, they differ in terms of where they can be placed on the dimension of compulsivity-impulsivity [25]. Whereas the disorders with primarily compulsive features, such as OCD, BDD and anorexia nervosa, are characterized by risk aversion, harm avoidance, increased serotonin function and underlying abnormalities in dorsal cortico-striatal neurocircuitry, disorders with predominantly impulsive features, such as pathological gambling, kleptomania and binge eating, are impulsive, driven by pleasure seeking and characterized by decreased serotonin function and underlying abnormalities in the ventral cortico-striatal circuitry [26]. In addition, many disorders, such as trichotillomania, autism and Tourette's disorder, are neither entirely compulsive nor impulsive; rather, to a large degree, they appear to share both compulsive and impulsive features [25].…”
Section: Compulsivity As a Core Symptom Of Ocdmentioning
confidence: 99%